DISRUPTION OF SUPPLY CHAIN FURNITURE INDUSTRY DURING CRISIS (Research Bulletins of the Faculty of Economic Sciences, 2024)
The aim of the article  is to analyze the place of distruption of supply chains in the production of the furniture industry in 2018-2021. The research problem – at what stages of the logistics supply chain of the furniture industry did breakage occur? The research hypothesis, it is assumed that the logistical supply chain of the furniture industry was broken at the stage of supply and distribution.
Keywords: supply chain, crisis, furniture industry